Women's sense of coherence and its association with early weaning - Fernando M. Cortelo; Sérgio T.M. Marba; Karine L. Cortellazzi; Glaucia M.B. Ambrosano; Luciane M. Guerra; Ana Cláudia G. Almeida; Scott L. Tomar; Margarete Ribeiro da Silva; Rosana F. Possobon (Elsevier, 2018)
Objective: To investigate whether there is an association between sense of coherence levels and early weaning. Method: This study had a quantitative nature and a cross-sectional design. Factors associated with early weaning (interruption of maternal breastfeeding) were investigated in a sample of 425 women older than 18 years, mothers of children up to 36 months of age who were not twins, with no sensory or motor deficiencies, without distinction of ethnicity or social class. The chi-squared test, with a significance level of 5%, was used to evaluate the association between the dependent variable (early weaning) and the independent variables (socioeconomic, demographic factors and sense of coherence level). Variables with p ≤ 0.20 were tested by the multiple logistic regression model. Odds ratio and the respective 95% confidence intervals were estimated. All statistical tests were performed using the SAS 9.2 software. Results: The results showed that mothers with greater sense of coherence were 1.82 times more likely to maintain breastfeeding for longer periods (p = 0.02). Conclusions: The identification of mothers with low sense of coherence allows the early intervention of health professionals, contributing to decrease the rates of early weaning in the population. Resumo: Objetivo: Investigar se há associação entre níveis de senso de coerência e desmame precoce. Método: O presente estudo tem natureza quantitativa e delineamento transversal. Foram investigados fatores associados ao desmame precoce (interrupção da oferta do leite materno á criança) em uma amostra de 425 mulheres com idade superior a 18 anos, sem distinção de etnia ou classe social, mães de crianças com até 36 meses, que não fossem gêmeos ou apresentassem deficiências sensoriais ou motoras. Foi feito o teste de qui-quadrado, com nível de significância de 5%, para testar a associação entre a variável dependente (desmame precoce) e as variáveis independentes (socioeconômicas, demográficas e nível de senso de coerência). As variáveis que apresentaram p ≤ 0,20 foram testadas no modelo de regressão logística múltipla. Os Odds Ratio e os respectivos intervalos de 95% de confiança foram estimados. Todos os testes estatísticos foram feitos pelo programa SAS 9.2. Resultados: Os resultados apontaram que mães com maior senso de coerência possuem 1,82 vez mais chance de manter o aleitamento por mais tempo (p = 0,02). Conclusões: A identificação de mães com baixo senso de coerência permite a intervenção precoce dos profissionais de saúde, contribui para diminuir as taxas de desmame precoce na população. Keywords: Sense of coherence, Breastfeeding, Weaning, Palavras-chave: Senso de coerência, Aleitamento, Desmame